Characterization of Alumina Nanoparticles Prepared Via Green Synthesis Method - Sahar Rashid; Shahbaa Bdewi; Eiman Alshammary; Ruaa Hammad (مجلة جامعة الانبار للعلوم الصرفة, 2023)
The green synthesis method of nanoparticles attracts the attention of researchers in various scientific specializations as it is easy, environmentally friendly, and low-cost. It is one of the important methods for preparing alumina nanoparticles, which has wide applications in various fields. In this work, alumina nanoparticles were prepared by this technique using an aluminum salt with a plant extract in the manner used in previous studies. The resulting nanoparticles were then characterized structurally and optically using several techniques. The results of X-ray diffraction (XRD) measurement proved the formation of alumina nanoparticles with a hexagonal phase through the peaks appearing in the diffraction pattern belonging to these nanoparticles, and it was found that their average particle size is equal to (61 nm). As for the scanning electron microscope images (SEM), it was shown that their diameters average range between (35 - 55 nm) and that their shapes are not arranged between spherical and rod-like, with the formation of aggregations of them. The results of measuring the UV-Vis spectrophotometer through the absorption spectrum showed that the surface plasmon resonance (SPR) of these nanoparticles at the wavelength (~300 nm). Fourier-transform infrared spectroscopy (FTIR) analysis distinguished the appearance of bonds belonging to alumina and within the range (~ 400 - 1100 cm-1).